COMPARISON OF LOW DOSE SHORT SYNACTHEN TEST (1 MICROGRAM) WITH STANDARD DOSE SHORT SYNACTHEN TEST (250 MICROGRAM) IN PATIENTS OF ADRENAL INSUFFICIENCY - Rana, Muhammad Zeeshan; Khan, Farooq Ahmad; Sattar, Abdus; Hashim, Rizwan (Pakistan Armed Forces Medical Journal, 2011)
Objective: To determine the diagnostic accuracy of low dose 1µg short synacthen test taking standard dose 250µg short synacthen test as gold standard. Study design: A descriptive study. Place and Duration of study: Department of Chemical Pathology & Endocrinology, Armed Forces Institute of Pathology Rawalpindi from Jan 2006 to Jan 2007. Patients and Methods: Thirty patients with clinical suspicion of adrenal insufficiency and equal number of age matched healthy males and females as controls were included in the study. Relevant clinical history and physical examination was recorded on designated proforma. Short synacthen test was performed between 0800 – 1000 h by using ACTH doses of 1µg and 250 µg with interval of 3 days in all patients and controls. Three blood samples were obtained for cortisol (basal, 30 min and 60 min after I/M ACTH injection). Results: Using 250µg short synacthen test as a standard test, the 1µg short synacthen test had sensitivity of 100 %, specificity of 72%, positive predictive value of 71 % and negative predictive value of 100 % and 83% accuracy. Conclusion: The low dose 1 µg short synacthen test is as sensitive as standard dose 250 µg short synacthen test but less specific in the diagnosis of adrenal insufficiency.